The Effect of Azotobacter on Growth and Yield of Water Spinach in Growing Media Containing Gold Mine Tailings - Erin April Felicia Silitonga; Reginawanti Hindersah; Betty Natalie Fitriatin (AGROLOGIA: Jurnal Ilmu Budidaya Tanaman, 2024)
Gold mining provides economic benefits but results in the conversion of agricultural land and produces low-fertility tailings. Efforts to remediate tailings can be done through the utilization of the biofertilizer bacteria Azotobacter sp., which is capable of producing exopolysaccharides. This study aims to study the effects of biofertilizers containing a consortium of Azotobacter sp. strains S5, S6a, and S9 in enhancing the growth and yield of water spinach plants in growth media containing gold mine tailings. The experiment used a randomized complete block design with four treatments and six replications. The treatments consisted of; (A) control, (B) 1% biofertilizer, (C) 5% biofertilizer, and (D) 10% biofertilizer. The results of the experiment showed that the dosage of 5% biofertilizers increased plant height, leaf count, and fresh weight of plants, while the 10% biofertilizer increased the stem diameter. The findings of this experiment emphasize the importance of biofertilizers in enhancing the growth and yield of water spinach plants in media with low fertility.